The role of pr activity in the structure of mass communications - Ravshan Rayimjanov (International Journal on Orange Technologies, 2021)
This article analyzes the relevance of information and mass communications, their impact on public opinion. It is emphasized that the media are a key link in the structure of mass communication. It has been also recognized that public relations as a new institution is an important element of mass communication, and many of its methods and tools have been analyzed.